2015
DOI: 10.1093/gerona/glv129
|View full text |Cite
|
Sign up to set email alerts
|

The Predictive Value of the EWGSOP Definition of Sarcopenia: Results From the InCHIANTI Study

Abstract: The EWGSOP's phenotype is a good predictor of incident disability, hospitalization and death. Assessment of only muscle weakness, in addition to low muscle mass, provided similar predictive value as compared to the original algorithm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
124
1
14

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 168 publications
(143 citation statements)
references
References 38 publications
4
124
1
14
Order By: Relevance
“…Low skeletal muscle mass, estimated by the crosssectional area of muscle on abdominal CT scan, a previously validated measure of sarcopenia in older adults (77), is independently associated with in-hospital mortality in older trauma ICU patients and adults receiving mechanical ventilation (78,79). These findings are consistent with prior studies in community-dwelling older adults showing low muscle mass increases the risk for subsequent disability and mortality (80)(81)(82).…”
Section: Biological Correlates Of Frailty In Critically Ill Adultssupporting
confidence: 85%
“…Low skeletal muscle mass, estimated by the crosssectional area of muscle on abdominal CT scan, a previously validated measure of sarcopenia in older adults (77), is independently associated with in-hospital mortality in older trauma ICU patients and adults receiving mechanical ventilation (78,79). These findings are consistent with prior studies in community-dwelling older adults showing low muscle mass increases the risk for subsequent disability and mortality (80)(81)(82).…”
Section: Biological Correlates Of Frailty In Critically Ill Adultssupporting
confidence: 85%
“…Sarcopenia is therefore considered a geriatric syndrome defined as a progressive impairment of muscle function due to the loss of skeletal muscle mass that occurs with advancing age (2). In older people, sarcopenia is a powerful risk factor for mobility impairment, disability, loss of independence, hospitalization, and death (3). The clinical implications of this geriatric syndrome have been reported consistently across different settings, including community-dwelling samples, nursing homes, and acute care departments (4).…”
mentioning
confidence: 99%
“…Later research however, demonstrated that, besides skeletal muscle mass, also muscle strength and/or physical performance were important in the clinical specification of sarcopenia. Since then, a revolution in the concept of the definition of sarcopenia had been set [3][4][5] . Several international research groups, including the European Working Group on Sarcopenia in Older People (EWGSOP), use these three determinants to present their clinical definition for the diagnosis of sarcopenia 6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…Sarcopenia is known to be associated with an increased risk for several adverse outcomes such as frailty, hospitalization, disability and mortality 4,13,14 . Especially the determinants muscle mass, muscle strength and physical performance have been found to play a major part in the increased risk of these adverse outcomes 4,5 . Also, sarcopenic patients with a diminished nutritional status have been shown to be at greater risk of dying in the shortterm 15 .…”
Section: Introductionmentioning
confidence: 99%